Pengaturan Tanah Baluwarti sebagai Kawasan Cagar Budaya yang Berbasis Budaya Hukum Jawa - Lego Karjoko (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
The aim of this research is to describe the regulation of Baluwarti land. As agreement between Surakarta government, Baluwarti society and keraton Surakarta relatives about the meaning of keraton Surakarta and the property of Baluwarti land. This research uses quality method with socio-legal study approach. The data consist if primary and secondary sort. The sources of the first data are keraton Surakarta relatives, the apparatus of Surakarta government and Baluwarti society, while the second are public and personeal data and the legally data. There were two ways to teke the primary data, namely observation and interview. Secondary had been gathered through library study, analysis of document, archives, primary and secondary legal data. Trianggulation method had been used to check the validity of data. The analysist consist of three ways used in the same moment, namely data reduction, data serve and verification. The interpretation had been used to understand the meaning of the information and the relation among it. The composition of the meaning relation depents on the thougt frame of the informant. As result of the discussion of this research is the harmonious opinion between Surakarta gavernment, Baluwarti society and keraton Surakarta reltives thet keraton Surakarta is the adat institution. It is also the guardian of Javanese culture and the tourism destinatiun. Each of them uses legal culture of Javanese as their frame of opinion. The opinion of part of keraton Surakarta relatives that keraton Surakarta is the governance center can’t be received. Such opinion isn’t compatable with the aspiration of Surakarta government and Baluwarti society. It is also able to cause the social violetry. There is a different opinion between keraton Surakarta relatives, government of Surakarta and Baluwarti society about the meaning of property of Baluwarti land. According to Baluwarti society and Surakarta government, Baluwarti land is the state property. On the other side, as for keraton Surakarta relatives, Baluwarti land is Sinuhun property delegated to Parentah Keraton Surakarta. But actually the three sides have the same interest. All of them hope that the existention of keraton Surakarta can give them economic constribution. The same interest is the foudation of the regulation of Baluwarti society as the cultural guardian. The source of Baluwarti land is the nation property, while Surakarta government regulates the relation between Sri Susuhunan and keraton relatives, person and corporation with Baluwarti land. The owner of Baluwarti property is Sri Susuhunan as the chief of keraton Surakarta relatives.